Consumer acceptance test and some related properties of selected KDML 105 rice mutants - Wangcharoen W. (2017)
© 2016, Association of Food Scientists & Technologists (India). Comparative analysis of the Kao Dawk Mali 105 (KDML 105) premium rice variety, and its six mutants, obtained after low energy ion bombardment, was carried out for sensory and other consumer acceptance related important properties. Consumer acceptance test (n = 200), colour parameters (L*, a*, b*), grain length, and texture parameters of cooked rice and 2-Acetyl-1-pyrroline (2AP), amylose, fat, and protein contents of polished rice were determined. The consumer acceptance test showed that HyKOS3-1 and KDML 105 were equally accepted for every attribute, while HyKOS16 had lower colour liking than KDML 105. Other mutants of KDML 105 were less accepted than KDML 105. Preference mapping (PCA bi-plot) showed that the overall liking of cooked rice was positively correlated to 2AP and fat content and negatively correlated to hardness, cohesiveness, springiness, chewiness, amylose and protein contents. Consumers preferred cooked rice which has good aroma and soft texture. However, only 2AP content might be not enough to explain aroma liking of cooked rice and rice with different texture could be accepted in the same level of KDML 105.